Internal Audit Capability Levels In Malaysian Public Sector Organizations: The Perceived Role Of Management Support And Cooperation With External Auditors - Nur Ain Zakiah, Mohd Yusof; Hasnah, Haron; Ishak, Ismail; Chambers, Andrew (Penerbit Universiti Malaysia Pahang, 2018)
This paper is a preliminary study as part of doctoral research. The primary objective of this paper is to measure the capability level of internal audit units of different organizations i.e. state department, state statutory bodies and federal statutory bodies. This paper also attempts to figuratively explain the perceived role of management support and cooperation with external auditors in becoming a capable internal audit function. A questionnaire, distributed to the head of internal audit in each organization, is used as a primary data collection method. From the analysis of internal audit capability matrix, it was found that internal audit unit in state department and federal statutory body both obtained capability level 2 (infrastructure) while internal audit unit in state statutory body only achieved capability level 1 (initial). At 82%, internal audit unit in state department scored highest for the Key Process Areas followed by internal audit unit in federal statutory body (76%) and state statutory body (71%). Management support and cooperation w ith external auditors were shown to be important factors to enhance capability levels. Factors that may influence capability level results and further recommendations on enhancing capability levels are discussed.